STUDIO DAN GALERI SENI ULM BANJARBARU - Wulandari, Lusi; Anhar, Pakhri (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
The ULM Banjarbaru Studio and Art Gallery is a forum for developing interests and talents which functions to accommodate all artistic activities within the ULM Banjarbaru campus, including the process of creating and displaying works. This is motivated by the unavailability of a special, integrated place to support the activities of students engaged in the arts. This Studio and Art Gallery also goes hand in hand with efforts to increase the competency of educational practices by the Ministry of Education, Culture, Research and Technology as well as UUD NO. 12 of 2012. The concept of "Expressionist Architecture" with a metaphorical approach is applied to design to produce free, dynamic and creative designs in accordance with meaning. art itself. By implementing concepts such as Dynamic Building Form, Flexible Area, and Spatial Expressions, buildings can become containers that have their own expression and are expected to support the manufacturing process so that the appearance of the work becomes more optimal so that it can become an educational and recreational medium for students and the wider community.